2003
DOI: 10.1093/gerona/58.1.m46
|View full text |Cite
|
Sign up to set email alerts
|

Step Training Improves the Speed of Voluntary Step Initiation in Aging

Abstract: A 3-week period of either voluntary or waist-pull-induced step training reduced step initiation time in older and younger adults. Moreover, compared with voluntary step practice, induced step training resulted in a significantly greater improvement in reaction time stepping for an auditory transfer cue task. At least in the short term, such step training has the potential to help older adults perform more like younger adults in their step initiation timing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 23 publications
2
67
0
2
Order By: Relevance
“…This underscores the contribution of other changes occurring in response to training beyond leg strength improvement, which could include psychological changes such as self-efficacy and -confidence [23] , reaction time [24] , or an interaction of factors related to movement and mobility.…”
Section: Discussionmentioning
confidence: 96%
“…This underscores the contribution of other changes occurring in response to training beyond leg strength improvement, which could include psychological changes such as self-efficacy and -confidence [23] , reaction time [24] , or an interaction of factors related to movement and mobility.…”
Section: Discussionmentioning
confidence: 96%
“…0.03). Rogers et al [21] found that a 3-week period of either voluntary or waist-pull-induced step training reduced step initiation time in older and younger adults. However, the findings of previous studies regarding the effects of exercise on step/gait initiation reaction times are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have examined the effects of exercising on step reaction times under single-task conditions [21] , and others have suggested including step training during dual-task conditions [22,23] in the elderly. An additional aim was to investigate the association between step execution behavior and self-reported physical function and balance performance in older persons.…”
mentioning
confidence: 99%
“…However, the task is difficult, and some elderly people cannot carry out this task. Rogers et al [26] reported their attempt to characterize the agility of elderly people by measuring the time before stepping begins in response to sensory stimulation. This method, however, requires a device for measurement and is hence somewhat complicated.…”
Section: Discussionmentioning
confidence: 99%